Визнання і виконання рішень іноземних судів та арбітражів на території України - Бундз, Ростислав; Bundz, Rostyslav (Видавництво Львівської політехніки, 2023)
У статті виокремлено актуальну проблему визнання та виконання рішень іноземних судів та арбітражів на території України – обставини, які унеможливлюють, чи ускладнюють таке виконання. Питання щодо визнання та виконання судових рішень іноземних держав в Україні сьогодні не втрачає своєї актуальності. Рішення іноземного суду визнається і виконується в Україні, якщо його визнання і виконання передбачено міжнародними договорами України. Рішення іноземного суду може бути примусово виконано в Україні протягом трьох років з дня набрання ним законної сили. Клопотання про надання дозволу на примусове виконання рішення іноземного суду подається в порядку, передбаченому міжнародними договорами України. Якщо зазначена заява та подані до неї документи не зареєстровані відповідно до вимог, передбачених законодавством, або до неї подано не всі необхідні документи, відповідний суд України повертає їх бенефіціару (його представнику) без розгляду. Питання про надання дозволу на примусове виконання рішення іноземного суду за клопотанням бенефіціара розглядається Апеляційним судом Автономної Республіки Крим, апеляційними обласними, Київським та Севастопольським міськими судами за місцем постійного чи тимчасового проживання або перебування (місцезнаходження) боржника. У разі неможливості визначення місцезнаходження боржника питання про надання допуску до примусового виконання рішення іноземного суду розглядається відповідним судом України за місцезнаходженням майна боржника в Україні. Процедура визнання та надання згоди на виконання рішень іноземних судів, виходячи з положень національного законодавства, є більш спрощеною за своїм змістом від аналогічної стосовно рішень міжнародних арбітражів держави пов’язана зі здійсненням захисту права фізичної та юридичної особи на підставі відповідного рішення на території України.

The article highlights the current problem of recognition and enforcement of decisions of foreign courts and arbitrations on the territory of Ukraine - circumstances that make such enforcement impossible or difficult. The issue of recognition and enforcement of court decisions of foreign states in Ukraine does not lose its relevance today. Decision of foreign court shall be recognized and executed in Ukraine, if its recognition and execution is envisaged by the international agreements of Ukraine. Decision of foreign court may be compulsory executed in Ukraine during three years starting from the day when it enters into force. Petition for granting permit to compulsory execution of decision of foreign court shall be submitted under the procedure, envisaged by the international agreements of Ukraine. If the above petition and documents submitted thereof are not registered in compliance with the requirements provided for by the legislation or not all necessary documents are submitted thereto, the respective court of Ukraine shall return them to the beneficiary (or its representative) without consideration. The issue related to grant of permit to compulsory execution of decision of foreign court under beneficiary's petition shall be considered by the Court of Appeal of the Autonomous Republic of Crimea, appeal oblast, Kyiv and Sevastopol city courts at the place of permanent or temporary residence or stay (location) of the debtor. If it is impossible to define location of the debtor, the issue related to grant of permit to compulsory execution of decision of foreign court shall be considered by the respective court of Ukraine at the place of location of debtor's property in Ukraine.The procedure for recognition and consent to the execution of decisions of foreign courts, based on the provisions of national legislation, is more simplified in its content than the similar procedure for decisions of international arbitrations.The need to recognize and enforce a court decision of a foreign state is related to the protection of the rights of individuals and legal entities on the basis of the corresponding decision on the territory of Ukraine.
Recognition and enforcement of decisions of foreign courts and arbitrations on the territory of Ukraine
Keywords: визнання; міжнародне співробітництво; виконання; судові рішення; іноземні суди; recognition; international cooperation; implementation; court decisions; foreign courts; 340.132